Electron-hole mechanism for the decomposition of zinc sulfide in a hydrogen atmosphere - Kharlamov V. F.; Styrov V. V.; Ilyin A. P. Aleksandr Petrovich; Gorfunkel' I. Z. (1976, 1976)
Chemical analysis is used to study the structural changes on the surface of a ZnS-Cu, Pb phosphor arising in the course of photoluminescence in molecular hydrogen and radical-recombination luminescence excited by hydrogen atoms. The photolysis of zinc sulfide and its decomposition by an atomic-molecular mixture of hydrogen were observed. A mechanism for the reduction involving electrons, holes, and chemisorbed hydrogen is discussed.